Analisis dan Perancangan Sistem Informasi Pelayanan Informasi Pasar Kerja Dengan Pendekatan Berorientasi Objek - Bambang Setiyawan; Ismiarta Aknuranda; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Labor Market Information Services is one of the services provided by the Department of Manpower (Disnaker)as meant in Regulation of the Minister of Manpower and Transmigration Republic of Indonesia Number 7 of 2008. Increasing job market information, job market, and expansion of employment opportunities and transmigration placement areas is one of the missions owned by Disnaker Malang Regency in line with the minister's regulation. Currently, labor market information services can be done by using the website of Disnaker Malang Regency. But by using this method, the labor market information service still needs to be maximized because the labor market information is mixed with other information. From these problems it is necessary to design an information system that supports in conducting labor market information service. Object Oriented Analysis and Design (OOAD) will be used in the analysis and design of the information system. The results of the analysis and design will be evaluated using the Requirements Configuration Structure and Decision table. The end result of this research is the current business process models and proposals, lists of stakeholders and users, user requirements list, features, system requirements list, use case model, system design and evaluation.